The Effect of Lesson Study for Learning Community Based Guided Inquiry Learning Model on Salt Hydrolysis Material on Student Learning Outcomes of SMAN 10 Padang - Tasya Dwi Azka Konita; Andromeda Andromeda (Entalpi Pendidikan Kimia, 2023)
The selection of learning models that have not been carried out optimally by educators so that a learning system is needed that supports this learning model. One learning system that can be applied is a lesson study-based learning system for learning communities. The key to the implementation of lesson study for learning community is in the reflection (see) stage so that the learning process has increased and has an impact on increasing teacher competence and improving student learning outcomes. The purpose of this study was to reveal the effect of the guided inquiry learning model based on lesson study for learning community on salt hydrolysis material on student learning outcomes of SMAN 10 Padang. This research is a quasi-experimental in the form of nonequivalent control group design. The analysis carried out obtained the results of data that were normally distributed and the variance was homogeneous so that it fulfilled the requirements of the t-test and obtained a sig(2-tailed) value of 0.001 < 0.05. Based on data analysis, it was concluded that the guided inquiry learning model based on lesson study for learning community on salt hydrolysis material has a significant effect on student learning outcomes.